STUDIES ON ANTI-HIV ACTIVITY OF PHYLLANTHUS EMBLICA PLANT EXTRACTS - VENKANNA LUNAVATH,; ESTARI MAMIDALA, (The Bioscan, 2012)
Human immunodeficiency virus type-1(HIV-1) is the cause of acquired immune deficiency syndrome (AIDS), a major human viral disease with about 33.2 million people infected worldwide. The high cost of the HAART regimen has impeded its delivery to over 90% of the HIV/AIDS population in the world. The aim of the present study was to evaluate the invitro anti- HIV activity of Phyllanthus emblica plant extracts. Extracts were prepared from dried fruit in n-hexane, ethyl acetate and n butanol. Peripheral Blood Mononuclear Cells (PBMCs) isolated from healthy donors by ficoll-hypaque density gradient centrifugation method. A toxicity study was performed on all crude extracts by MTT assay using PBMCs isolated from whole blood. HIV-1 RT inhibition activity of the all solvent extracts of Phyllanthus emblica was determined. AQF and HXF fractions show highest inhibition of recombinant HIV-RT (91% and 89% respectively) at 1 mg/mL concentration. Chloroform (CFF) fraction shows highest inhibition of HIV-RT at 0.5 mg/mL and Carbon tetra chloride (CTF) fraction at 0.12 mg/mL concentration. The highest non-cytotoxic concentration (>95% cell viability) of HXF, CTF, CFF and AQF fractions are 0.02, 0.04, 0.02 and 0.02 mg/mL respectively. At 0.12 mg/mL and 0.5 concentrations 50% of the HIV-RT activity is inhibited in HXF and CTF fractions respectively. The fruit of Phyllanthus emblica extracts are shows anti-HIV-1 activity and this plant has great potential for developing useful drugs.